2002
DOI: 10.2337/diabetes.51.5.1609
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Known and Unknown Susceptibility Genes to Early-Onset Diabetes in Scandinavia

Abstract: In an attempt to identify novel susceptibility genes predisposing to early-onset diabetes (EOD), we performed a genome-wide scan using 433 markers in 222 individuals (119 with diabetes) from 29 Scandinavian families with >2 members with onset of diabetes <45 years. The highest nonparametric linkage (NPL) score, 2.7 (P < 0.01), was observed on chromosome 1p (D1S473/D1S438). Six other regions on chromosomes 3p, 7q, 11q, 18q, 20q, and 21q showed a nominal P value <0.05. Of the EOD subjects in these 29 families, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…No other genome-wide scans of MODY families have been published (with the exception of the five Swedish families in this study that were part of a young-onset type 2 diabetes genome-wide scan) (26), and so we cannot look for regions of linkage overlapping with ours using the same phenotype. Additional early-onset families with type 2 diabetes have been identified (42,43), and our regions will provide starting places for any future genome-wide screens of MODYX or early-onset type 2 diabetic families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No other genome-wide scans of MODY families have been published (with the exception of the five Swedish families in this study that were part of a young-onset type 2 diabetes genome-wide scan) (26), and so we cannot look for regions of linkage overlapping with ours using the same phenotype. Additional early-onset families with type 2 diabetes have been identified (42,43), and our regions will provide starting places for any future genome-wide screens of MODYX or early-onset type 2 diabetic families.…”
Section: Discussionmentioning
confidence: 99%
“…These include regions on chromosome 4 and 20 (45) in Ashkenazi Jews, chromosome 6 in Finnish subjects ranging in age at diagnosis from 29 to 44 years (46), chromosome 5 in Swedish subjects (47), chromosome 3 in French subjects diagnosed with type 2 diabetes before 45 years of age (48), chromosomes 5 and 22 in U.K. subjects from families where the average age at diagnosis was Ͻ45 years (49), and chromosomes 1, 5, 7, 8, 11, 15, and 21 in Swedish/Finnish subjects (26). Although it is not clear from all these studies the exact ages at diagnosis, most appear to represent subjects diagnosed under the age of 45 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two research groups (14,15) have reported linkages for diabetic nephropathy on 18q. Lindgren et al (16) found suggestive linkage on 18q12 for early-onset diabetes. A locus for type 1 diabetes (IDDM6, MIM 601941) also mapped to 18q21 (17).…”
mentioning
confidence: 99%
“…Shaw et al (47) observed a susceptibility locus for late-onset type 2 diabetes linked to marker D12S321 (65 cM) on chromosome 12, with an LOD score 3.65. In early-onset diabetic Scandinavians (48), an NPL score of 1.9 was documented on chromosome 18 near marker D18S535 (64 cM). This marker is 16 cM upstream of our signal for 2-h insulin concentrations.…”
Section: Resultsmentioning
confidence: 99%